Accessing and sustaining social tenancies : Exploring barriers to homelessness prevention /: Exploring barriers to homelessness prevention. (September 2016) - Campbell, Jacqueline; Golten, Adam; (Researcher on homelessness), Jackson, Rebecca; (Researcher on homelessness), Evans, Richard
No abstract available